Airlines in transition - Taneja, Nawal K. (Lexington Books LexingtonUS, 1981)
Explores the impact of escalating fuel prices, high inflation and interest rates, up- and down-surveys in the US economy, and the declining value of the US dollar, on the airline in the decade of the eighties.